Formation of styrene monomer, dimer and trimer in the primary volatiles produced from polystyrene pyrolysis in a wire-mesh reactor - Zhou, J.; Qiao, Y.; Wang, W.; Leng, E.; Huang, J.; Yu, Yun; Xu, M. (Elsevier Ltd, 2016)
© 2016 Elsevier Ltd.This paper reports the formation of styrene monomer, dimer and trimer in the primary volatiles during fast pyrolysis of polystyrene in a wire-mesh reactor where secondary reactions of primary pyrolysis volatiles are minimized. Styrene monomer is the most abundant product in the primary volatiles from polystyrene pyrolysis, with a selectivity of 48-69 wt% depending on pyrolysis temperature, while dimer and trimer only have selectivities of 8-10 and 9-30 wt%, respectively. High temperature promotes the formation of styrene monomer and suppresses the formation of styrene trimer, but with little effect on the formation of styrene dimer. It is also found that the selectivities of styrene monomer, dimer and trimer show negligible changes with increasing the conversion level at the same pyrolysis temperature. The results suggest neither 1,3-hydrogen transfer nor intermolecular benzyl radical addition is the dominant formation mechanism for styrene dimer. The styrene dimer is more likely produced via the 1,7- and 7,3-hydrogen transfer mechanism.